Efektivitas Permainan Ular Tangga Dalam Meningkatkan Kemampuan Konsep Ruang Bagi Anak Autisme - Alda Zahara Islamyati; Ardisal (Ranah Research : Journal of Multidisciplinary Research and Development, 2020)
This research has done based on autism children X problem at SLB Khansa Padang. The purpose of this research is to increase the ability of right and left rom concept through snakes and ladders game. This research used Single Subject Research (SSR) method with A-B-A design. A1 is early condition or before intervention, B is intervention, A2 is a condition when children have no longer in intervention. On baseline 1 (A1) continuously in 5 times of meetings until datas in stable condition. Interventions through snakes and ladders game has done in 8 times of meetings untul data in stable condition and baseline condition (A2) has given in 3 times of meetings to see the influence of intervention on ability of children's room concept. This research used direct observation as data collection method such as test, interview, observation, and documentation. The result of this research is to prove that sankes and ladders game could improve the ability of autism children X rom concept.